Determine which solution is correct for solving startfraction 5 over 7 endfraction y = 6using reciprocals. Startfraction 5 over 7 endfraction y = 6 (startfraction 5 over 7 endfraction y) minus (startfraction 7 over 5 endfraction) = 6 minus (startfraction 7 over 5 endfraction) (6) y = startfraction 42 over 5 endfraction (startfraction 5 over 7 endfraction) (startfraction 5 over 7 endfraction y) = (startfraction 5 over 7 endfraction) (6) y = startfraction 23 over 5 endfraction startfraction 5 over 7 endfraction y = 6 y = startfraction 30 over 7 endfraction startfraction 5 over 7 endfraction y = 6 (startfraction 7 over 5 endfraction) (startfraction 5 over 7 endfraction y) = 6 startfraction 5 over 7 endfraction y = 6 (startfraction 7 over 5 endfraction) (startfraction 5 over 7 endfraction y) = (startfraction 7 over 5 endfraction) (6) y = 6.